2011
DOI: 10.1093/schbul/sbr178
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Metabolic Dysfunctions by Prenatal Immune Activation in Mice: Relevance to Schizophrenia

Abstract: Schizophrenia is associated with increased risk for multiple metabolic abnormalities, including altered glucose homeostasis, type-2 diabetes, obesity, and cardiovascular disease. Some of the metabolic alterations can already exist in psychosis-prone subjects prior to the onset of chronic schizophrenic disease and pharmacotherapy, indicating that they may have a developmental origin. In the present study, we tested the hypothesis that metabolic alterations pertinent to schizophrenic disease can be primed by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
7
32
0
Order By: Relevance
“…The adult emergence of poly(I:C)--induced PPI deficit is consistent with numerous previous studies in mice (e.g., Lipina et al, 2013;Pacheco--López et al, 2013;Vuillermot et al, 2010) and rats ; but see also Wolff and Bilkey, 2010). Since the hippocampal formation is one of several neuronal substrates modulating sensorimotor gating (Bast and Feldon, 2003), deficient hippocampal expression of presynaptic proteins may readily contribute to the attenuation of PPI in immune--challenged offspring.…”
supporting
confidence: 89%
“…The adult emergence of poly(I:C)--induced PPI deficit is consistent with numerous previous studies in mice (e.g., Lipina et al, 2013;Pacheco--López et al, 2013;Vuillermot et al, 2010) and rats ; but see also Wolff and Bilkey, 2010). Since the hippocampal formation is one of several neuronal substrates modulating sensorimotor gating (Bast and Feldon, 2003), deficient hippocampal expression of presynaptic proteins may readily contribute to the attenuation of PPI in immune--challenged offspring.…”
supporting
confidence: 89%
“…Moreover, long-term metabolic abnormalities have also been observed in mouse offspring of mothers that were exposed to the viral mimetic polyriboinosinic-polyribocytidilic acid (polyI:C), a synthetic analog of double-stranded RNA that induces a virus-like acute phase response (93). In this virus-like immune activation model, offspring of polyI:C-treated mouse dams were shown to develop altered glycemic regulation and abnormal ingestive behavior in adolescence and excess fat deposition in adulthood (115). Similar results were obtained in a mouse model, in which pregnant mice were infected with Ljungan virus (LV), a virus that belongs to the Picornavirus family and is virulent for laboratory rodents (126).…”
Section: Obesity and Metabolic Dysfunctionsmentioning
confidence: 99%
“…Some studies using rodent models of bacterial or viral maternal immune challenge have reported a significant upregulation of circulating inflammatory factors such as proinflammatory cytokines or chemokines in the juvenile or adult offspring (17,43,69). Other studies using the same animal models, however, failed to find clear signs of systemic inflammation in juvenile or adult offspring born to immunologically challenged mothers (96,157), or they even reported opposite effects that were characterized by blunted systemic inflammatory activity following prenatal infection (115).…”
Section: Peripheral (And Central) Inflammationmentioning
confidence: 99%
See 2 more Smart Citations